Modeling of Talent Acquisition for Organizational Development - Sadique Shaikh; Mamta Dahad (Journal of Model Based Research, 2019)
In this work, we try to explain the concept of human talent with the help of some equations and models, which are not generated by any one previously. Here we also trying to explain ‘human talent is not resources it’s itself one of the great sources to find out all possible resources’. Because we cannot predict human talent directly, to judge it, we should have to adapt some methods for talent acquisition, which we explained with the help of models and equations. How human talent is one of the great source, if we want to know it, we have to observe human behavior, wits and intelligence strictly by working simultaneously with them. In this work our conclusion is ‘human talent natural and dynamic in nature’ and can be easily diverted to perform any task. Where as machine and technology has programmed memory, logics i.e. artificial intelligence (AI), and hence in result talent is fixed and constant in nature and only able to do repetitive and fixed task and also for proper handling and utilization of machines and technology need arises of human talent. In last only want to mentioned work is very useful in all HRM and OB practices.
Keywords: Talent Acquisition